THE INFLUENCE OF BUSINESS INTELLIGENCE ON IMPROVING MARKETING PERFORMANCE IN THE DIGITAL ERA - Sudiantini, Dian; Danu, Julian; Setyakinasti, Sabrina; Permatasari, Selvia Annisa; Ottay, Merry Louis; Putri, Cinka Amalia (LPPM Institut Pendidikan Nusantara Global, 2024)
Businesses should adapt to digital competition, anticipate consumer needs, and innovate to stay ahead. This study aims to examine the influence of business intelligence on enhancing marketing performance in the digital era, building upon previous research on the impact of social media on innovation. Further investigation is necessary to understand the effects of technology on marketing effectiveness. This paper used qualitative research to explore concepts in depth, collecting descriptive data through observation and analyzing events using intensive techniques. Data analysis involves organizing and categorizing data, recognizing patterns, and drawing conclusions. Business intelligence is an e-business app that converts company data into knowledge, enhancing competitiveness. Data analysis is crucial for boosting a company's business performance, converting raw data in the data warehouse into valuable information.